Microarray platform affords improved product analysis in mammalian cell growth studies. Issue 3 (19th December 2013) - Datta, Payel; Meli, Luciana; Li, Lingyun; Migliore, Nicole; Schaefer, Eugene; Sharfstein, Susan T.; Dordick, Jonathan S.; Linhardt, Robert J.
Abstract High throughput (HT) platforms serve as a cost‐efficient and rapid screening method for evaluating the effect of cell‐culture conditions and screening of chemicals. We report the development of a HT cell‐based microarray platform to assess the effect of culture conditions on Chinese hamster ovary (CHO) cells. Specifically, growth, transgene expression and metabolism of a GS/methionine sulphoximine (MSX) CHO cell line, which produces a therapeutic monoclonal antibody, was examined using a microarray system in conjunction with a conventional shake flask platform in a non‐proprietary medium. The microarray system consists of 60‐nL spots of cells encapsulated in alginate and separated in groups via an 8‐well chamber system attached to the chip. Results show the non‐proprietary medium developed allows cell growth, production, and normal glycosylation of recombinant antibody and metabolism of the recombinant CHO cells in both the microarray and shake flask platforms. In addition, 10.3 mM glutamate addition to the defined base medium results in lactate metabolism shift in the recombinant GS/MSX CHO cells in the shake flask platform. Ultimately, the results demonstrate that the HT microarray platform has the potential to be utilized for evaluating the impact of media additives on cellular processes, such as cell growth, metabolism, and productivity.